Sports activity in functional systems theory - N. A. Fudin; Yu. E. Vagin (Сеченовский вестник)
The article discusses organizational patterns of athletes’ functional activity from the functional systems theory prospective. The psychological and physiological processes in athletes determine their activities and are aimed at sports results achievement. Athletes' physiological capacity is in turn determined by the motivation, sports skills, external information, emotions and coach’s instructions. The sequence in the intermediate and ﬁnal sports results achievement by athletes is described from the prospective of behavioral systemic quantization concept. The process of improving athletic performance is combined in a continuum of athletes’ training and competitive activities. The fatigue processes in athletes' viscera and functional systems are analyzed in their dynamic interrelation. The article demonstrates the eﬃciency of the systemic approach to analyze athletes' reserve capacity increase resulting from fatigue and physical performance decrease resulting from overfatigue.